2015
DOI: 10.1088/0004-637x/805/1/76
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Formation of Carbonaceous Refractory Matter in High Temperature Hydrocarbon-Rich Atmospheres of Exoplanets Upon Micrometeoroid Impact

Abstract: We report on laboratory simulation experiments mimicking the chemical processing of model atmospheres of exoplanets containing C3 and C4 hydrocarbons at moderate temperatures of 400 K upon interaction of catalytic surfaces of micrometeoroids. By utilizing an ultrasonic levitator device and heating singly levitated particles under simulated microgravity conditions, Raman spectroscopy is utilized as a non-invasive tool to probe on line and in situ the conversion of C3 and C4 hydrocarbons to refractory carbonaceo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 41 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Recently, Lorenzi et al (2016) suggested that the discoloration of Pluto along with Makemake and Eris may be due to COMs, and our present study shows that this is very likely just from the simple ethane ice. Dangi et al (2015) has shown that under model atmospheric conditions containing C3 and C4, hydrocarbons interact catalytically with surfaces of micrometeroids to produce a carbonaceous refractory layer, which can account for the hydrocarbon sequestration.…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
“…Recently, Lorenzi et al (2016) suggested that the discoloration of Pluto along with Makemake and Eris may be due to COMs, and our present study shows that this is very likely just from the simple ethane ice. Dangi et al (2015) has shown that under model atmospheric conditions containing C3 and C4, hydrocarbons interact catalytically with surfaces of micrometeroids to produce a carbonaceous refractory layer, which can account for the hydrocarbon sequestration.…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
“…Furthermore, a levitator can be used to probe the differences between the physical and chemical processes on the bulk samples and the surfaces of sub-millimeter size levitated particles. 5 , 12 Such tiny particles floating in the given gas medium provide ideal laboratory conditions simulating the dust particles or droplets in the atmospheres of planets and exoplanets. 5 Moreover, the levitated particle can respond quickly to temperature and radiation perturbations due to their small total heat and radiation dose capacity.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 12 Such tiny particles floating in the given gas medium provide ideal laboratory conditions simulating the dust particles or droplets in the atmospheres of planets and exoplanets. 5 Moreover, the levitated particle can respond quickly to temperature and radiation perturbations due to their small total heat and radiation dose capacity. Hence, a levitation device provides a versatile platform to study the physical and chemical processes without support structures as well as creates less-contingent sample trapping requirements, such as electric charge and refractive index.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations